(untitled) (Indian Journal of Animal Production and Management, 2024)
The present study aimed to estimate juvenile body measurements in indigenous Uttara (U) chicken and comparisons of their estimates with Rhode Island Red (RIR), Kadaknath (K) and Australorp (A) breed of chickens using 400 day-old chicks. The parameters were estimated for juvenile body weight was recorded on an electronic balance in the morning before feeding on 0 to 20 week at 2 weeks intervals. The growth rate of Uttara is higher than that of Kadaknath and Australorp but at certain stages similar to that of RIR. Further, an investigation aimed to evaluate body conformation characteristics at 12 and 20 weeks of age. Conformation traits are higher in RIR in comparison to other chicken breeds, but at certain stages, Uttara shows a similar trend as that of RIR. Furthermore, data on adult body weight and egg production measurements were estimated. Egg production of Uttara is better than other breeds. Thus, early body measurements of the Uttara chickens can be used for prediction of the size of the adult Uttara. These research-outcomes may serve as base information to the breeders and academicians for chalking outbreeding strategy in the concerned aspect.